Effectiveness in the omega 3 (Fish) and vitamin D supplementation during the gestational period for the prevention of various allergies in the 0-1 year old infant - Vargas Gómez, Dennia (2017)
The objective of this research was to describe the effectiveness of omega 3 (fish) and vitamin D supplementation during the gestational stage for the prevention of various allergies in infants aged 0 to 1 year. The results of a compilation and categorization of the best available scientific evidence are presented. The methodology suggested for the clinical practice based on the evidence was applied, which began with the establishment of a clinical question followed by the search of the information in the Medline, Science Direct and Cochrane Library databases, obtaining 334 articles of which when the selection criteria are applied, they are kept 9. Then, a critical analysis was carried out using the FLC 2.0 platform and the evidence was classified by its quality and degrees of recommendation according to the Canadian Task Force on Preventive Health Care. It is concluded that although the benefits of vitamin D and omega 3 are multiple, and that the joint use of both in pregnancy, could mean an improvement not only on maternal health but also on the fetus and infant; By not having studies with conclusive results, it can not be generalized or recommended in clinical practice.